Determinants Of Rating/Share Of Indonesian Television News In The Online Era (The Case Of Mnctv Indonesia) - Arifin Saleh Harahap; Mulyadi, Mulyadi; Machyudin Agung Harahap; Ballian Siregar; Euis Nurul Bahriyah; Andry Susanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The purpose of this study is to identify a plan for sustaining and growing MNCTV news stations' share and rating. This television news station has been around for around 27 years and is still going strong. Despite the fact that the generation at this news station has shifted, this is inextricably linked to the outstanding program rating/share and has a tendency to remain steady. Descriptive qualitative research methodology is used to gather detailed information about the chief editor and three executives involved in news programs. The findings demonstrated that from pre-production to post-production, the editorial team holds regular meetings. Reporters with specialized knowledge of the issue being covered are provided access to all of the materials reviewed during the editorial meeting. Additionally, they stay up to date with technology advancements to improve the screen. To improve the on-screen presentation, news anchors are frequently swapped out for younger, more intelligent candidates. As the times change, news is also posted to official social media profiles on platforms like YouTube, Instagram, and TikTok.